The human in bits : graphical computers, Black abstractions / Kris Cohen. - Cohen, Kris, 1972- (Duke University Press, 2025)
Kris Cohen examines Black abstractionist painting to demonstrate how race and computation are intimately entangled in the graphic user interface of the personal computer.